2017
DOI: 10.1007/s11701-017-0725-x
|View full text |Cite
|
Sign up to set email alerts
|

Health care cost consequences of using robot technology for hysterectomy: a register-based study of consecutive patients during 2006–2013

Abstract: The objective of this study is to examine the costs attributable to robotic-assisted laparoscopic hysterectomy from a broad healthcare sector perspective in a register-based longitudinal study. The population in this study were 7670 consecutive women undergoing hysterectomy between January 2006 and August 2013 in public hospitals in Denmark. The interventions in the study were total and radical hysterectomy performed robotic-assisted laparoscopic hysterectomy (RALH), total laparoscopic hysterectomy (TLH), or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
2
1
Order By: Relevance
“…Smith et al reported that the overall hospital charge was 40% higher with RMIS compared to laparoscopy and open access surgery [31]. In contrast to our findings, Laursen et al found that RMIS generated cost savings of $3861 per women when compared with open access surgery and increased costs of €$3749 when compared with laparoscopy in Danish cancer patients [32]. Important differences between the study of…”
Section: Discussioncontrasting
confidence: 91%
“…Smith et al reported that the overall hospital charge was 40% higher with RMIS compared to laparoscopy and open access surgery [31]. In contrast to our findings, Laursen et al found that RMIS generated cost savings of $3861 per women when compared with open access surgery and increased costs of €$3749 when compared with laparoscopy in Danish cancer patients [32]. Important differences between the study of…”
Section: Discussioncontrasting
confidence: 91%
“…We believe that in the optimal setting, RALAC can be a safe and cost-effective approach to abdominal cerclage [20,27]. The ideal time to perform an abdominal cerclage is before pregnancy; however, similar efficacy of laparoscopic and abdominal cerclage has been reported regardless of the timing of the procedure, and our experience echoes these findings.…”
Section: Discussionsupporting
confidence: 72%
“…Multiple studies have suggested a higher cost of robotic surgery compared with benign laparoscopic gynecologic surgery [23][24][25]. Others have shown equal costs or benefits to robotic gynecologic surgery when taking into additional factors, such as hospital stay, complications, established robotics in the hospital, and surgeon expertise, even when compared with other minimally invasive approaches [26,27]. When a robot is already available in a surgical setting, the cost of robotic surgery drops drastically and similar hospital cost can be attained for laparoscopy and robotics [28].…”
Section: Discussionmentioning
confidence: 99%
“…61 There is, therefore, no overall consensus regarding the cost-effectiveness of robot-assisted surgery when compared to other approaches for gynaecological procedures. 12,62,63 Cost-effectiveness analyses are complex and are severely limited due to variations in the surgeries compared, the techniques and instruments used, and the experience of the surgeon. 12 Furthermore, global differences in health care economics and health care models used (public or private) mean that total costs, and therefore cost-effectiveness, will vary significantly between countries utilizing robot-assisted surgery.…”
Section: Discussionmentioning
confidence: 99%